Studying of Structural Properties of ZnxNi1-x-yCuyFe2O4 Spinel Ferrite Using XRD Powder - Abdil Majeed, Ahmed R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
ZnxNi1-x-yCuyFe2O4 spinel ferrite were prepared using solid state reaction method with (y=0.1, x=0.2, 0.3, 0.4, 0.5, 0.6 ) . X-ray diffraction with diffractometer CuKÎ± analysis have been carried out and studied showing single phase spinel cubic with space group FDÍž 3m for all prepared samples . Lattice parameters and crystallite grain size and x-ray density(Ïx-ray) bulk density and porosity ratio's were calculated and showed good agreement with the international data reported in the scientific research's.